Japan - Sabelko, Rebecca (Blastoff! readers. Countries of the world., 2023)
"Made up of over 6,000 islands, Japan is full of exciting attractions for visitors and residents alike! In this book, young readers are introduced to Japan and its landscape, wildlife, population, foods, sports, holidays, and more. Alongside leveled text and vibrant images, maps, profiles, and other special features provide even more detail about this beautiful country." -- Amazon.com.